Antioxidant and Antimicrobial Activity of New Amide Compounds Containing Azo Group Using Dicyclohexylcarbodiimide (DCC) as Coupling Agent - Saleh, Dania Mohammed; Al-Salami, Bushra Kamel (Universitas Gadjah Mada, 2025)
A series of amide compounds (A2D1-A2D6) were synthesized based on sulfathiazole by converting it to diazonium salt using NaNO2 and concentrated HCl via diazotization reaction. This reaction was followed by coupling reaction with vanillic acid in alkaline medium to generated azo compound 4-hydroxy-3-methoxy-5-((4-(N-(thiazol-2-yl)sulfamoyl)phenyl)diazenyl)-benzoic acid (A2). Compound A2 was reacted with substituted aromatic amines such as 2-amino-4,6-dimethylpyridine, sulfamerazine, sulfadiazine, sulfanilamide, sulfathiazole, and sulfanilic acid to form corresponding amides using DCC as coupling reagent to be promoted condensation reaction. The structures of synthesized compounds have been diagnosed with elemental analysis, FTIR, 1H-NMR, 13C-NMR, and mass spectrometry. The antibacterial activities for all new synthetic compounds was estimated accurately depending on selected bacteria such as Staphylococcus aureus (Gram-positive) and Escherichia coli (Gram-negative) using different concentrations to calculate minimum inhibition concentration. The effectiveness of inhibiting fungi was also studied against Candida albicans by agar diffusion method. Finally, the antioxidant capacities of the prepared compounds were determined by using DPPH radical scavenging method. The results of potential radical scavenging activity were given as IC50. The compounds showed strong biological activity and good antioxidant activity compared with the standard substance Vitamin C.